Prediction of tensiomyography on jumping performance in male gymnasts - Marinsek, M.; Namestnik, S.; Samardzija Pavletic, M. (International Scientific Congress Slovenian Gymnastics Federation, 2019)
This study examined the association between muscles` contractile characteristics and jumping skill performance in male gymnasts. Seventeen internationally experienced male gymnasts participated in the study. Radial displacement (Dm) and contractile time (CT) of the biceps femoris (BF), rectus femoris (RF), vastus lateralis (VL), vastus medialis (VM), and erector spinae (ES) were collected to assess muscles` contractile characteristics using tensiomyography (TMG). Additionally, peak power value (PP), jump height (JH), and vertical take-off velocity (Vy) in squat jump (SJ), countermovement jump (CMJ), and drop jump (DJ) were recorded. The TMG parameters did not predict jumping performance in our sample of men gymnasts. Associations between TMG parameters and jumping performance are discussed in the article.